1974
DOI: 10.1002/j.1556-6978.1974.tb00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Counselor Training Models: A Comparative Study

Abstract: This study investigated the effects of three prepracticum counselor training approaches on counselor performance: T group, behavioral skills, and discussion control. Pre‐ and postmeasures consisting of 30‐minute video‐recorded counseling interviews were administered to all subjects. Counselor performance was evaluated by client completion of the Counseling Evaluation Inventory (CEI) and by three trained judges' ratings of four five‐minute interview segments using the Counseling Strategies Checklist (CSC). Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
3
8
0
Order By: Relevance
“…Cormier, Hackney, and Segrist (1974) have reported similar results. They compared the skill development of prepracticum counseling students assigned to three different treatment groups: (l) a discussion control, (2) a T-group, and (3) a behavior skills group.…”
Section: Skills Vs Self As Instrumentsupporting
confidence: 86%
“…Cormier, Hackney, and Segrist (1974) have reported similar results. They compared the skill development of prepracticum counseling students assigned to three different treatment groups: (l) a discussion control, (2) a T-group, and (3) a behavior skills group.…”
Section: Skills Vs Self As Instrumentsupporting
confidence: 86%
“…However, Cormier, Hackney, and Segrist (1974) found that systematic behavioral skills training, an approach that closely parallels MC in its specification of target skills and sequential use of programmed texts, modeling, and videotaped rehearsal with feedback, was no more effective than discussion group or encounter group approaches. This may be due to the investigators' attempt to teach a variety of moderately difficult skills to novice prepracticum students, rather than focusing on a limited number of discrete counselor responses.…”
Section: Micro Counseling (Mc)mentioning
confidence: 96%
“…That effect remains best described by Rogers (1 957) as the necessary and sufficient conditions of therapeutic change. For some time, research has suggested that reliance on training in skills usage rather than personal development is most likely to produce effective counsellors (Cormier, Hackney & Segrist, 1974;Toukmanian & Rennie, 1975). To this end, skill-based training programmes encompassing procedures for measuring the usage of these skills have been developed (e.g., Ivey & Authier, 1978).…”
Section: Introductionmentioning
confidence: 98%